Pengaruh Konflik dan Job Description Terhadap Semangat Kerja Karyawan - Lestari, Ni Putu Diana; Mashyuni, Ida Ayu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
To maintain and increase employee morale, proper and fast strategies must be implemented such as how to handle conflicts and appropriate job descriptions. The purpose of this study was to examine the effect of conflict and job description on employee morale in CV. Motion Cafe Canggu, Badung. In this research, the data collection method used is the method of observation, interviews, documentation, literature and questionnaires. The sample used in this study were 57 respondents. Test instruments used in this study were validity and reliability tests, then hypothesis testing was carried out by using multiple linear Regreis analysis techniques. The results of this study are (1) conflict partially has a positive and significant effect on employee morale, (2) job description partially has a positive and significant effect on employee morale, and conflict and job description simultaneously have a positive and significant effect on employee morale.